مزاح سے متعلق اسلامی و مغربی مفکرین کی آراء اور نبوی ﷺتعلیمات ؛ایک تجزیاتی مطالعہ : Views of Islamic & Western Scholars about Humour and Propheticﷺ Teachings; An Analytical Study - Hussain, Wasif; Mahmood, Dr. Khalid; Farooq , Muhammad Umar (Al-Amīr Research Journal for Islamic Studies, 2023)
Fun and humour are part of human nature and character while people have a strong desire for relaxation that they want to have the means to express joy. Even bitter ideas can be easily conveyed to others through humor and good nature. Islam did not only allow laughter and entertainment but also prescribed such rules and regulations that people can fulfill their natural needs while living within the limitations. The Holy Prophet ﷺ made the best arrangements for Islamic state of Madina, the tastes and interests of the people, and their entertainment, and set an example for the rulers that like other countries. Hazrat Muhammad ﷺ did not only allow laughter and humor, but he himself was cheerful and happy towards his companions. Humour is an essential element of human life, and it has significant importance in Islam as well as in other religions. In this regard, we also get a lot of guidance from Sirat-e-Tayyaba, and it is justified with certain conditions. In this article, the authors have discussed the introduction of humor, its status in Shariah and its limitations from the perspective of Islamic Shari’ah. The authors have tried to analysis opinions of psychologists, Islamic and Western thinkers in this regard. Keywords: Cheerfulness, Humor, Human Instinct, Entertainment Humiliation.